2012
DOI: 10.1182/blood-2012-06-440057
|View full text |Cite
|
Sign up to set email alerts
|

Kininogen deficiency protects from ischemic neurodegeneration in mice by reducing thrombosis, blood-brain barrier damage, and inflammation

Abstract: Thrombosis and inflammation are hallmarks of ischemic stroke still unamenable to therapeutic interventions. Highmolecular-weight kininogen (KNG) is a central constituent of the contact-kinin system which represents an interface between thrombotic and inflammatory circuits and is critically involved in stroke development. Kng Ϫ/Ϫ mice are protected from thrombosis after artificial vessel wall injury and lack the proinflammatory mediator bradykinin. We investigated the consequences of KNG deficiency in models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 51 publications
9
125
1
1
Order By: Relevance
“…20,21,[33][34][35][36] Taken together with our findings, these studies indicate that DMT targeting should be achieved as soon as possible following occlusion, even before recanalization, to be effective. In that regard, a recent EVT meta-analysis showed that the likelihood of a favorable outcome increased with the use of previous intravenous thrombolysis with alteplase.…”
Section: Strokementioning
confidence: 66%
“…20,21,[33][34][35][36] Taken together with our findings, these studies indicate that DMT targeting should be achieved as soon as possible following occlusion, even before recanalization, to be effective. In that regard, a recent EVT meta-analysis showed that the likelihood of a favorable outcome increased with the use of previous intravenous thrombolysis with alteplase.…”
Section: Strokementioning
confidence: 66%
“…Brains were quickly removed and embedded for cryosections. 45 To analyze apoptosis, the in situ Cell Death Detection Kit, TMR red was used according to the manufacturer's instructions.…”
Section: Stroke Modelmentioning
confidence: 99%
“…Also downstream of plasmakallikrein, absence of high molecular weight kininogen has been shown to be protective after transient middle cerebral artery occlusion. Indeed, Langhauser et al 46 recently identified high molecular weight kininogen as key mediator of experimental…”
Section: Contact-kinin Pathwaymentioning
confidence: 99%